Criminal Sanction Reduction Policy: Mental and Intellectual Disabilities Review from the Purpose of Punishment - Rugun Romaida Hutabarat (Jurnal Dinamika Hukum, 2024)
In the realm of criminal law, it is acknowledged that criminal offenses may be perpetrated by a broad spectrum of individuals, including those with disabilities, spanning both mental and intellectual realms. The term “disability” includes individuals with physical or intellectual impairments who could not previously be sanctioned. However, Law No. 1 of 2023 has provided for the imposition of sanctions for people with mental or intellectual impairments. This study employs a normative research methodology, utilizing a statutory approach through the examination of various literature and journals focused on criminal law policy. Specifically, it addresses the implementation of incarceration for individuals with mental and intellectual disabilities. Through descriptive-analytical methods, this research highlights that Article 38 of the New Criminal Code expands the scope of criminal sanctions applicable to individuals with mental and intellectual disabilities. This provision appears to be at odds with Article 44 of the Criminal Code, which exempts persons with such disabilities from criminal liability, suggesting a contradiction where Article 38 permits the application of reduced penalties. The conclusion posits that while individuals with disabilities might be seen as not fully accountable under certain circumstances, leading to exemption from criminal penalties, a human rights perspective advocates for prioritizing social rehabilitation.